Studi Literatur Uji Stabilitas Fisik Berbagai Sediaan Berbasis Ekstrak Daun Kencur (Kaempferia galanga L.) - Aida Savitri; Sri Muliany; Regina Nabila; Nor Latifah (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Galangal (Kaempferia galanga L.) is a herbal plant known to have anti-inflammatory, antibacterial, and antioxidant activities. The use of galangal extract in topical pharmaceutical preparations such as ointments, gels, and creams requires attention to the physical stability of the preparation to ensure the effectiveness and safety of the product. This study aims to examine the physical stability of various forms of galangal extract-based preparations through literature studies from three relevant journals. The method used is a descriptive literature study by analyzing the results of physical stability tests (organoleptic, pH, homogeneity, spreadability, adhesion, and viscosity) of ointments, gels, and creams. The results of the study showed that the gel form with a carbopol base provided the best overall physical stability, followed by an ointment with a water-washed base. Meanwhile, sunscreen cream made from galangal and seaweed showed quite good stability, although its spreadability and adhesion still need to be improved. This study provides an overview that the form and composition of the preparation greatly affect the physical stability of galangal extract, as well as the importance of choosing the right base in the formulation.